First-Principles Study on Structural, Electronic and Elastic Property of ZnS Nanotubes (Journal of Atomic and Molecular Sciences, 2013)
The structural, stability and elastic property of single-walled ZnS nanotubes(SW-ZnS NTs) with armchair and zigzag forms were investigated using first-principlesapproaches. We have investigated a size dependence of stability and elastic modulus in SW-ZnS NTs. It is found that both the stability and the Young’s modulus aredecrease dramatically with increasing diameter and proportional to the Zn-S bondlength.
Keywords: density functional theory; nanotube; stability; elastic modulus.